2017
DOI: 10.2737/fpl-rp-692
|View full text |Cite
|
Sign up to set email alerts
|

Statistical models for the distribution of modulus of elasticity and modulus of rupture in lumber with implications for reliability calculations

Abstract: It is common practice to assume that a two-parameter Weibull probability distribution is suitable for modeling lumber properties. Verrill and co-workers demonstrated theoretically and empirically that the modulus of rupture (MOR) distribution of visually graded or machine stress rated (MSR) lumber is not distributed as a Weibull. Instead, the tails of the MOR distribution are thinned via "pseudotruncation." The theoretical portion of Verrill's argument was based on the assumption of a bivariate normal-Weibull … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…In section 4.2 of Verrill et al (2017) we noted that graphical evidence from the 200-piece sample suggested that bivariate stiffness-strength data might have approximately the distribution of a mixture of two bivariate normal distributions. We further noted that this would explain the good separate fits of mixtures of univariate normals to the stiffness data and to the strength data.…”
Section: A Fit Of a Mixture Of Bivariate Normals To Lumber Stiffness-...mentioning
confidence: 98%
See 4 more Smart Citations
“…In section 4.2 of Verrill et al (2017) we noted that graphical evidence from the 200-piece sample suggested that bivariate stiffness-strength data might have approximately the distribution of a mixture of two bivariate normal distributions. We further noted that this would explain the good separate fits of mixtures of univariate normals to the stiffness data and to the strength data.…”
Section: A Fit Of a Mixture Of Bivariate Normals To Lumber Stiffness-...mentioning
confidence: 98%
“…However, these assumptions are based on the work of researchers who were fitting distributions to grades of lumber (as in the In-Grade work) rather than to mill run populations. This fact, and the need for an accurate estimate of the MOR probability density function in reliability calculations, led us to perform the experiment described in Verrill et al (2017) and Owens et al (2018) -an experiment designed to yield estimates of mill run bivariate stiffness-strength distributions (which, in turn, yield estimates of pseudo-truncated MOR distributions).…”
Section: A Fit Of a Mixture Of Bivariate Normals To Lumber Stiffness-...mentioning
confidence: 99%
See 3 more Smart Citations